(untitled) (Journal of Medical & Health Sciences Review, 2025)
Hypertension is a complex genetic disorder with numerous genetic and environmental factors. Essential hypertension is recognized as a global health concern, which remarkably increases the possibility of the development of cardiovascular and kidney diseases. This condition ranks as the 13th leading cause of death in the United States and has a global prevalence rate of 33, with a notably higher rate of 46.2% among the Pakistani population. Among the various biological Pathways, the Renin-Angiotensin-Aldosterone System (RAAS) is one of the most important pathways involved in blood pressure regulation. Being an essential component of RAAS, the Single Nucleotide Polymorphisms (SNPs) in the AGT gene are thoroughly studied in connection to hypertension in different populations across the globe. This study aimed to investigate the association between AGT polymorphism (rs699) and hypertension using a case-control study in a Pakistani Population from the district Nowshera. Blood samples were collected from 224 study subjects (112 hypertensive patients and 112 controls), and DNA was extracted using a non-enzymatic salting-out method. An Amplification Refractory Mutation System-Polymerase Chain Reaction (ARMS-PCR) based genotyping method was developed and utilized to determine the genotypes of the study subjects. The resultant genotypic and allelic frequencies were statistically tested for association with Hypertension through Chi-squared and Fisher’s exact tests using Prism-GraphPad software. The study revealed no significant association between the SNP (rs699) and hypertension in our sample set (P = 0.3802, χ² = 1.934). Including additional SNPs and a large sample size is likely to provide regional insights into the genetic basis of hypertension.